Samorządowe inwestycje w województwie dolnośląskim w latach 2000-2006 - Maciejuk, Marian (Investments of Local Authorities in Lower Silesia Region in the Period of 2000-2006, 2008)
The study presents the diversification of investment outlays at three levels of local authorities units in Lower Silesia region, i.e. in communes, districts and the self-government region in the period of 2000 - 2006. The diversification is presented with regard to the structure of investment outlays, their dynamics, their overall share in budget expenditure, investment outlays per 1 inhabitant as well as sources and directions of financing investments. The research covers all types of communes: urban communes (33 units), rural communes (79 units) and urban-rural ones (54 units), as well as rural districts (26 units), townships (3 units) and also the self-government region. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 470-478